COMMON RISK FACTORS INVOLVED IN THE DEVELOPMENT OF MYOCARDIAL INFARCTION IN ADULTS YOUNGER THAN 45 YEARS OF AGE - Faisal Iftikhar; Shazia Tauqeer; Sahar Farhat; Muhammad Orakzai; Raisa Naz; Abdur Rehman (Journal of Ayub Medical College Abbottabad, 2022)
Background: Pakistan has got a very high prevalence of myocardial infarction (MI). MI presents at pretty young age in this country. The objective of present study was to determine the frequency of common risk factors associated with early development of MI in middle aged adults of less than 45 years. Methods: It was a cross sectional study conducted in the Cardiology department of Ayub Teaching Hospital (ATH) Abbottabad from 23rd June 2015 - 10th July 2016. A total of 255 consecutive patients diagnosed with MI admitted to the Cardiology Unit of ATH, Abbottabad. A detailed medical history and general physical examination of the patients was carried out with an emphasis on recording the presence or absence of common risk factors of MI in these patients. All routine investigations (Blood Complete Picture, Urea, Creatinine, Blood Sugar & Lipid Profile) were done. Results: Mean age of the subjects was 39.98±4.61 SD. The frequency of risk factors in descending order was smoking in (38.8%), obesity in (29.4%) and essential hypertension in (21.6%) of the patients. Other risk factors of MI in this study were diabetes mellitus (19.2%), family history of ischemic heart disease (IHD) was (18.8%) and disproportionate dyslipidemias in (12.9%). Sex of patients (male predominance) was found to be significantly associated with diabetes, smoking and dyslipidemia (p<0.05). Conclusion: Male sex, smoking, hypertension and obesity confer an increased risk of myocardial infarction in patients younger than 45 years of age.